Algorithms in Bioinformatics 14th International Workshop, WABI 2014, Wroclaw, Poland, September 8-10, 2014. Proceedings - Brown, Dan; Morgenstern, Burkhard (Lecture Notes in Bioinformatics, 2014)
This book constitutes the refereed proceedings of the 14th International Workshop on Algorithms in Bioinformatics, WABI 2014, held in Wroclaw, Poland, in September 2014. WABI 2014 was one of seven conferences that were organized as part of ALGO 2014. WABI is an annual conference series on all aspects of algorithms and data structure in molecular biology, genomics and phylogeny data analysis. The 26 full papers presented together with a short abstract were carefully reviewed and selected from 61 submissions. The selected papers cover a wide range of topics from sequence and genome analysis through phylogeny reconstruction and networks to mass spectrometry data analysis.